High performance composites and methods for making the same

CN123003271APending Publication Date: 2026-10-30CHANGZHI CARBON VALLEY TECH INCUBATOR CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611327227.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-08-29
Filing Date
2026-08-28
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]现有传统高性能复合材料普遍存在原料成本高、制备工艺复杂的不足;而采用工业固废制备复合材料的技术路线,又面临矿相调控难度大、基体与增强相之间界面结合力差等技术难题

Benefits of technology

本申请通过调控碳还原剂种类及用量,搭配金属氧化物与助熔剂,经高温、超高温两步热处理构建非平衡碳热还原反应环境;该反应环境有利于精准调控产物矿相,降低矿相调控难度,实现复合材料各项性能协同提升。本申请所得产物为单一粉料,可保障后续成型加工过程的结构稳定性,同时简化制备流程,实现复合材料的低成本制造。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to a high-performance composite material and a preparation method thereof. The preparation method of the high-performance composite material comprises the following steps: preparing raw materials, regulating and controlling the raw materials to comprise 70-80 parts of silicon-aluminum-based oxides, at least 12 parts of carbon reducing agents, 0.5-2 parts of fluxing agents and at least 6 parts of other metal oxides in terms of weight parts, wherein the silicon-aluminum-based oxides comprise SiO2 and Al2O3; grinding the raw materials to obtain ground raw materials; carrying out high-temperature treatment on the ground raw materials in an inert environment to obtain pretreated raw materials; carrying out ultrahigh-temperature treatment on the pretreated raw materials to obtain semi-reduced-state materials; and processing the semi-reduced-state materials to obtain the high-performance composite material. The application has the effects of improving heating efficiency in the preparation process, realizing performance synergistic optimization and low-cost manufacturing of the composite material, and simultaneously improving the difficulty of mineral phase regulation and control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a high-performance composite material and a method for preparing the same. Background Technology

[0002] High-temperature structural materials are a class of structural materials suitable for use in high-temperature environments. Some high-temperature structural materials also possess properties such as wear resistance and thermal conductivity. They typically include high-temperature alloys, intermetallic compounds, and composite materials. Among these, composite materials include metal matrix composites, ceramic matrix composites, and carbon / carbon composites.

[0003] Composite materials are used in high-tech fields such as new energy equipment, aerospace, and metallurgy, which place stringent requirements on the high temperature resistance, electrical conductivity, wear resistance, thermal conductivity, density, and cost control of the composite materials used.

[0004] Existing traditional high-performance composite materials generally suffer from high raw material costs and complex preparation processes; while the technical route of preparing composite materials using industrial solid waste faces technical challenges such as difficulty in mineral phase control and poor interfacial bonding between the matrix and the reinforcing phase. Summary of the Invention

[0005] In order to improve the heating efficiency in the preparation process, achieve synergistic optimization of composite material properties and low-cost manufacturing, and improve the difficulty of mineral phase control, the purpose of this application is to provide a high-performance composite material and its preparation method.

[0006] Firstly, the method for preparing a high-performance composite material provided in this application adopts the following technical solution: A method for preparing a high-performance composite material includes the following steps: S1. Prepare raw materials. By weight, the raw materials include 70-80 parts of silicon-aluminum oxide, at least 12 parts of carbon reducing agent, 0.5-2 parts of flux, and at least 6 parts of other metal oxides, wherein the silicon-aluminum oxide includes SiO2 and Al2O3. S2. Grind the raw material to obtain ground raw material; S3. The grinding material is subjected to high temperature treatment in an inert environment to obtain pretreated material; S4. The pretreated raw material is subjected to ultra-high temperature treatment to obtain a semi-reduced material; S5, high-performance composite materials obtained by semi-reduced material processing.

[0007] Optionally, the grinding material described in steps S3 and S4 may fall in an inert environment.

[0008] Optionally, the raw materials for preparation include: Take at least one of coal gangue, fly ash, and diabase to determine the composition of the material; Based on the measured material composition, the content of carbon reducing agent is adjusted using the content of silicon-aluminum oxide as a benchmark. Add the flux.

[0009] Optionally, the other metal oxides mentioned in step S1 include at least one of Fe2O3, TiO2, CaO, MgO, K2O, and Na2O.

[0010] Optionally, grinding the raw material in step S2 includes grinding the raw material to a particle size ≤200 μm.

[0011] Optionally, step S3, which involves subjecting the grinding material to high-temperature treatment in an inert environment, includes: In an inert gas environment, set the temperature to 1800-2300℃ and process for 5-10 minutes.

[0012] Optionally, the ultra-high temperature treatment of the pretreated raw material in step S4 includes: The temperature should be controlled at no less than 3000℃, and the residence time of the pretreated raw materials should be 0.5-1s; Preferably, the pre-treated raw materials are subjected to ultra-high temperature treatment using a Joule heating device.

[0013] Optionally, the semi-reduced material is processed to obtain a high-performance composite material, including low oxygen partial pressure combined with electromagnetic disturbance treatment. The low oxygen partial pressure combined with electromagnetic disturbance treatment includes: The semi-reduced material is placed in a sealed reaction vessel and subjected to electromagnetic disturbance in an inert atmosphere for 6-10 seconds per cycle. The temperature is controlled at 1350-1450℃ and the treatment lasts for 18-30 minutes to obtain a high-performance composite material.

[0014] Secondly, this application provides a high-performance composite material.

[0015] A high-performance composite material was prepared using a high-performance composite material preparation method.

[0016] In summary, this application includes at least one of the following beneficial technical effects: This application constructs a non-equilibrium carbothermic reduction reaction environment by controlling the type and amount of carbon reducing agent, combined with metal oxides and fluxes, and through a two-step heat treatment process of high temperature and ultra-high temperature. This reaction environment facilitates precise control of the product mineral phase, reduces the difficulty of mineral phase control, and achieves synergistic improvement of various properties of the composite material. The product obtained by this application is a single powder, which can ensure the structural stability of subsequent molding and processing, while simplifying the preparation process and realizing low-cost manufacturing of composite materials. Detailed Implementation

[0017] <Implementation Plan 1> Embodiment 1 of this application provides a method for preparing high-performance composite materials, including the following steps: S1. Prepare raw materials. By weight, the raw materials include 70-80 parts of silicon-aluminum-based oxide, at least 12 parts of carbon reducing agent, 0.5-2 parts of flux, and at least 6 parts of other metal oxides, of which the silicon-aluminum-based oxide includes SiO2 and Al2O3.

[0018] In this technical solution, the silicon-aluminum based oxides are mainly SiO2 and Al2O3.

[0019] Carbon reducing agents refer to carbon-containing compounds that can reduce metal oxides at high temperatures. Common examples include coke, graphite, coal, charcoal, carbon nanofibers, carbon black, and activated carbon.

[0020] Calcium fluoride can be used as a flux. By adding the flux, calcium fluoride melts and spreads at high temperatures, encapsulating carbon particles to form a catalytic interface and reducing the activation energy of the carbothermic reduction reaction during subsequent high-temperature processing. Simultaneously, the addition of the flux can effectively lower the reaction temperature of silicon-aluminum based oxides.

[0021] Other metal oxides include at least one of Fe2O3, TiO2, CaO, MgO, K2O, and Na2O, as long as they can be reduced under high-temperature conditions in conjunction with a carbon reducing agent.

[0022] In one specific technical solution, the preparation of raw materials is achieved through the following steps: At least one of coal gangue, fly ash, and diabase is selected to determine the material composition. In this technical solution, coal gangue, fly ash, and diabase are all rich in silicon-aluminum based oxides, and also include a variety of other metal oxides, basically meeting the requirements for the proportion of silicon-aluminum based oxides and other metal oxides, which can be adjusted according to actual conditions; Based on the measured material composition, the carbon reducing agent content is adjusted using the silicon-aluminum oxide content as a benchmark. In this technical solution, coal gangue usually contains a sufficient amount of carbon reducing agent, but fly ash and diabase contain little or no carbon reducing agent. Based on the test results, the carbon reducing agent is supplemented to at least 12 parts.

[0023] Add the flux.

[0024] S2. After grinding the raw material, a ground raw material is obtained.

[0025] In this technical solution, grinding the raw materials includes grinding the raw materials to a particle size ≤200 μm to obtain uniform powder.

[0026] S3. The grinding material is subjected to high temperature treatment in an inert environment to obtain pretreated material.

[0027] This technical solution includes: in an inert gas environment, setting the temperature to 1800-2300℃, and processing for 5-10 minutes. Specifically, in one technical solution, taking the plasma flame device as an example, it can be set to use an Ar / H2 mixed gas (volume ratio 9:1) as the working gas, and process at a high temperature of 1800-2300℃ for 5-10 minutes, specifically by using a descent method.

[0028] By adopting the above technical solution, since other metal oxides are uniformly distributed inside the grinding material, a heat conduction network is formed from the outside to the inside during the falling process. During the heating process, the auxiliary heating body promotes the reduction of other metal oxides, improves temperature uniformity, and reduces local overheating. Specifically, taking Fe2O3 as an example, it can promote the reduction of Fe2O3 to the metal phase; taking TiO2 as an example, it can promote the reaction of some TiO2 with carbon to generate TiC crystal nuclei.

[0029] S4. The pretreated raw materials are subjected to ultra-high temperature treatment to obtain semi-reduced materials.

[0030] In this technical solution, the step of subjecting the pretreated raw materials to ultra-high temperature treatment includes: The temperature should be controlled at no less than 3000℃, and the residence time of the pretreated raw materials should be 0.5-1s.

[0031] In one specific technical solution, the pre-treated raw materials are subjected to ultra-high temperature treatment using a Joule heating device.

[0032] Using the above technical solution, the pretreatment raw materials are subjected to ultra-high temperature treatment in an inert atmosphere (Ar or N2). The internal metal phase of the pretreatment raw materials is used to achieve efficient heating, which effectively reduces the silicon-aluminum oxide and provides a precursor for mineral phase control during subsequent molding. This ensures the structural stability of the molding process. At the same time, the carbothermic reduction reaction is accelerated to generate intermediate products such as SiO(g), FeO, and TiC.

[0033] S5, high-performance composite materials obtained by semi-reduced material processing.

[0034] The semi-reduced material is processed to obtain a high-performance composite material, including low oxygen partial pressure combined with electromagnetic disturbance treatment.

[0035] The low oxygen partial pressure combined with electromagnetic disturbance treatment includes: The semi-reduced material is placed in a sealed reaction vessel and subjected to electromagnetic disturbance in an inert atmosphere for 6-10 seconds per cycle. The temperature is controlled at 1350-1450℃ and the treatment lasts for 18-30 minutes to obtain a high-performance composite material.

[0036] This application also provides a high-performance composite material, which is prepared using the above-described method for preparing high-performance composite materials.

[0037] Example 1 A method for preparing a high-performance composite material includes the following steps: S1. Prepare raw materials. By weight, the raw materials include 70-80 parts of silicon-aluminum-based oxide, at least 12 parts of carbon reducing agent, 0.5-2 parts of flux, and at least 6 parts of other metal oxides, of which the silicon-aluminum-based oxide includes SiO2 and Al2O3.

[0038] In this step: S1.1 The composition of coal gangue was determined as shown below; Al2O324.402%, SiO249.802%, MgO 0.033%, K2O 2.139%, CaO 2.998%, TiO20.887%, MnO 0.07%, Fe2O32.825%, ZnO 0.007%, Rb2O 0.009%, SrO 0.03%, Y2O30.004%, ZrO20.029%, P2O50.093%, SO30.689%, C 15.981%.

[0039] Taking 1 kg of the aforementioned coal gangue as an example, the material usage is calculated as follows: the corresponding content of silicon-aluminum based oxides is 74.204 parts (742.04 g); the content of carbon reducing agent is 15.981 parts (159.81 g); and the content of other metal oxides, including MgO, K2O, CaO, TiO2, MnO, Fe2O3, ZnO, Rb2O, SrO, Y2O3, and ZrO2, is 9.031 parts (90.31 g). S1.2 Add 0.5-2 parts of flux.

[0040] In this step, add 1.25 parts (12.5g) of calcium fluoride.

[0041] S2. Grind the raw material to a particle size ≤200 μm to obtain the ground raw material.

[0042] S3. The grinding material is subjected to high temperature treatment in an inert environment (1800-2300℃, treatment for 5-10 min) to obtain pretreated material.

[0043] This step includes: The grinding material was placed in a plasma flame device, and the Ar / H2 mixed gas (volume ratio 9:1) was used as the working gas. The material was subjected to a high temperature of 2000℃ for 8 minutes to obtain pretreated material.

[0044] S4. The pretreated raw materials are subjected to ultra-high temperature treatment to obtain semi-reduced materials.

[0045] This step includes: A Joule heating device is used to control the temperature at no less than 3000℃ in an inert atmosphere (Ar / N2), and the pre-treated raw material falls and stays for 1 second.

[0046] S5, high-performance composite materials obtained by semi-reduced material processing.

[0047] This step includes: The semi-reduced material was placed in a sealed reaction vessel and subjected to electromagnetic disturbance in an inert atmosphere for 20 minutes at a time period of 8 seconds, with the temperature controlled within the range of 1350-1450℃.

[0048] Example 2 A method for preparing a high-performance composite material. Similar to Example 1, except that the operation method of step S1.1 is different, specifically: S1.1 The composition of fly ash was determined as shown below; A12O335.6%, SiO246.5%, Na2O 0.567%, MgO 0.667%, K2O 1.58%, CaO 4.42%, TiO21.52%, Cr2O30.0371%, MnO 0.0446%, Fe2O36.04%, NiO 0.0161%, CuO 0.0135%, ZnO0.0527%, Ga2O30.0106%, As2O30.0242%, SeO20.0037%, Rb2O 0.0084%, SrO 0.116%, Y2O30.0087%, ZrO20.0379%, PbO 0.0158%, ThO20.0066%, P2O50.252%, SO32.37%, Cl 0.105%.

[0049] Taking 1 kg of the above-mentioned fly ash, the corresponding content, based on the content of silicon-aluminum oxides, is converted and confirmed to be 82.1 * 0.90 = 73.89 parts (821 g); other metal oxides, including Na2O, MgO, K2O, CaO, TiO2, Cr2O3, MnO, Fe2O3, NiO, CuO, ZnO, Ga2O3, As2O3, SeO2, Rb2O, SrO, Y2O3, ZrO2, PbO, and ThO2, have a content of 15.1899 * 0.90 = 13.67 parts (151.899 g). The carbon reducing agent in the fly ash was supplemented to 12 parts (133.333g) using graphite powder.

[0050] Comparative Example 1 A method for preparing a composite material. Similar to Example 1, except that step S32 high-temperature treatment is not included, that is, the grinding material is not placed in a plasma flame device and treated at 2000°C for 8 min with an Ar / H2 mixed gas (volume ratio 9:1) as the working gas. Instead, the grinding material is directly subjected to the ultra-high temperature treatment in step S4.

[0051] Comparative Example 2 A method for preparing a composite material. Same as Example 2, except that it does not include "the carbon reducing agent in fly ash is supplemented to 12 parts using graphite powder".

[0052] Comparative Example 3 A method for preparing a composite material. Same as Example 1, except that it does not include "adding 1.25 parts of calcium fluoride".

[0053] Analysis shows that: (1) Selective acid leaching was performed on the semi-reduced materials of Examples 1, 2, and Comparative Examples 1-2 to separate the target reduced phase based on the solubility differences of different phases (oxidized / reduced) in a specific leaching agent; then, the content of the reduced metal phase was determined by ICP quantitative determination, thereby analyzing the proportion of reduced Al, Si, and Fe, as shown in Table 1 below: Table 1 As shown in Table 1, the proportion of reduced Al, Si and Fe in Comparative Example 1 is significantly lower than that in Example 1. The main reason is that the grinding raw materials in Comparative Example 1 are not subjected to high-temperature treatment, but are directly subjected to ultra-high temperature treatment, so that other metal oxides cannot be effectively reduced before ultra-high temperature treatment, thus failing to cooperate with the subsequent ultra-high temperature treatment to construct a non-equilibrium carbothermal reduction reaction environment.

[0054] In Comparative Example 2, almost no reduced Al, Si, and Fe were detected. This is because, compared to Example 2, no carbon reducing agent was added to Comparative Example 2, which resulted in it being unable to effectively promote the reduction of other metal oxides at high temperatures and also inhibiting the reduction of Al, Si, and Fe at ultra-high temperatures.

[0055] (2) Compared with Example 1, Comparative Example 3 does not include calcium fluoride, cannot encapsulate carbon particles to form a catalytic interface, and cannot effectively reduce the activation energy of the carbothermic reduction reaction during subsequent Joule heating.

[0056] The embodiments described herein are preferred embodiments of this application and are not intended to limit the scope of protection of this application. Identical components are indicated by the same reference numerals. Therefore, all equivalent changes made to the structure, shape, and principle of this application should be included within the scope of protection of this application.

Claims

1. A method for preparing high-performance composite materials, characterized in that, Includes the following steps: S1. Prepare raw materials. By weight, the raw materials include 70-80 parts of silicon-aluminum oxide, at least 12 parts of carbon reducing agent, 0.5-2 parts of flux, and at least 6 parts of other metal oxides, wherein the silicon-aluminum oxide includes SiO2 and Al2O3. S2. Grind the raw material to obtain ground raw material; S3. The grinding material is subjected to high temperature treatment in an inert environment to obtain pretreated material; S4. The pretreated raw material is subjected to ultra-high temperature treatment to obtain a semi-reduced material; S5, high-performance composite materials obtained by semi-reduced material processing.

2. The method for preparing high-performance composite materials according to claim 1, characterized in that, The grinding materials described in steps S3 and S4 fall in an inert environment.

3. The method for preparing high-performance composite materials according to claim 1, characterized in that, The raw materials used in the preparation include: Take at least one of coal gangue, fly ash, and diabase to determine the composition of the material; Based on the measured material composition, the content of carbon reducing agent is adjusted using the content of silicon-aluminum oxide as a benchmark. Add the flux.

4. The method for preparing high-performance composite materials according to claim 1, characterized in that, The other metal oxides mentioned in step S1 include at least one of Fe2O3, TiO2, CaO, MgO, K2O, and Na2O.

5. The method for preparing high-performance composite materials according to claim 1, characterized in that, The grinding of the raw material in step S2 includes grinding the raw material to a particle size ≤200 μm.

6. The method for preparing high-performance composite materials according to claim 1, characterized in that, Step S3, which involves subjecting the grinding material to high-temperature treatment in an inert environment, includes: In an inert gas environment, set the temperature to 1800-2300℃ and process for 5-10 minutes.

7. The method for preparing high-performance composite materials according to claim 1, characterized in that, Step S4, which involves subjecting the pretreated raw material to ultra-high temperature treatment, includes: Set the control temperature to be no lower than 3000℃ and the residence time of the pretreated raw materials to 0.5-1s.

8. The method for preparing high-performance composite materials according to claim 1, characterized in that, The pre-treated raw materials are subjected to ultra-high temperature treatment using a Joule heating device.

9. The method for preparing high-performance composite materials according to claim 1, characterized in that, The semi-reduced material is processed to obtain a high-performance composite material, including low oxygen partial pressure combined with electromagnetic disturbance treatment. The low oxygen partial pressure combined with electromagnetic disturbance treatment includes: The semi-reduced material is placed in a sealed reaction vessel and subjected to electromagnetic disturbance in an inert atmosphere for 6-10 seconds per cycle. The temperature is controlled at 1350-1450℃ and the treatment lasts for 18-30 minutes to obtain a high-performance composite material.

10. A high-performance composite material, characterized in that, It is prepared using the method for preparing high-performance composite materials as described in any one of claims 1-9.